Telehealth Therapy for Therapists: Barriers and Benefits. (July 2020) - Botaitis, Nicole; Southern, Stephen
Personal therapy for therapists is described as a means for advancing personal and professional growth. Therapist problems contribute to boundary disturbance, ethical violation, and incompetence. Benefits of therapy include enhanced counselor reflection and therapeutic alliance. Telehealth therapy overcomes barriers and represents an innovation in self-care and career development.